2001
DOI: 10.1136/vr.149.4.115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of renal tubular dysplasia, a new hereditary disease in Japanese Black cattle

Abstract: A new hereditary disease characterised by renal failure, poor growth and long hooves in Japanese Black cattle (wagyu) has been recognised in a region of central Japan since 1990. The number of calves affected has increased gradually, with the incidence reaching 17 of 485 (3.51 per cent) in 1995. Almost all the calves were slightly undersized at birth, and repeatedly had diarrhoea during the neonatal period. They began to show signs of growth retardation with proportional body and elongation of the hooves from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Physical examination indicated that all the cattle were in fairly good condition. Hereditary renal tubular dysplasia [9] and bovine viral diarrhea virus infection [10], both of which cause growth retardation, were excluded by gene analyses. Propionate (Wako Pure Chemical Industries, Tokyo) reagents were adjusted to 0.625 mmol/kg (pH 7.4).…”
mentioning
confidence: 99%
“…Physical examination indicated that all the cattle were in fairly good condition. Hereditary renal tubular dysplasia [9] and bovine viral diarrhea virus infection [10], both of which cause growth retardation, were excluded by gene analyses. Propionate (Wako Pure Chemical Industries, Tokyo) reagents were adjusted to 0.625 mmol/kg (pH 7.4).…”
mentioning
confidence: 99%
“…It is also known as "renal tubular dysplasia in Japanese Black cattle" [13][14][15][16][17] or "bovine chronic interstitial nephritis with diffuse zonal fibrosis" [5,8]. This disease is caused by a homozygous deletion of gene and is transmitted by autosomal recessive inheritance [8,14].…”
mentioning
confidence: 99%
“…In bovines, although studies of the CL-16 defect in the genetic field have developed considerably [5,8,[13][14][15][16][17][18], pathology of the defect remains to be elucidated. The purpose of this study was to clarify the histopathological characteristics of the CL-16 defect and conditions that lead to renal failure, and to examine the distribution of CL-16 protein immunohistochemically.…”
mentioning
confidence: 99%
“…Additionally, hereditary diseases involved in growth retardation, such as renal tubular dysplasia (RTD) [16] and red blood cell-band 3 deficiency [6], are also known to afflict Japanese black cattle. However, more detailed knowledge of the causes for insufficient growth of cattle has yet to be obtained.…”
mentioning
confidence: 99%